Intercultural Education in School and Recognition of the Other - Sousa, Isabela Cabral Félix de (Education Policy Analysis Archives, 2004)
This article describes a potential project of intercultural education for schools. It begins by emphasizing the growing importance of this kind of project in an era of globalization. Then, I describe some educational proposals toward the construction of a new way to look to oneself and "the other." Third, I discuss the possibility that a project of this nature may be resisted since it challenges the status quo. Finally, the article stresses that the implementation of this project depends on educational policies and the efforts of the total society.